Juden und ihre Nachbarn Die Wissenschaft des Judentums im Kontext von Diaspora und Migration - Schoor, Kerstin; Treß, Werner (Europäisch-jüdische Studien - Beiträge, 2022)
The contributions in this volume address developments in the emergence of a Jewish scholarship movement against the backdrop of diaspora and migration movements in Central and Eastern Europe. These studies on the epistemology of scholarly practices, on the genesis of methods and concepts, and exchange between theoretical approaches reveal the developments that took place in the Wissenschaft des Judentums (Jewish Scholarship) movement.